ANALISIS KEKUATAN POROS LANDING GEAR PESAWAT N-219 - Nizar Malendes; Stenly Tangkuman; Tritiya Arungpadang (Fakultas Teknik Jurusan Teknik Mesin Universitas Sam Ratulangi, 2016)
The aim of this study is to analyze the strength of the shaft of the landing gear aircraft N-219 against the variation of cargo’s weight. The examined object in this study is the landing gear of N-219 aircraft produced by PT Dirgantara Indonesia. The static strength analysis was conducted on the stress and maximum deflection to the shaft of the landing gear N-219 aircraft. The results of this study showed that the variation of cargo’s weight affects the strength of the landing gear shaft where the increase of the cargo’s weight will result in a linear increase of deflection and stress. Finally, the allowed maximum weight of the N-219 aircraft cargo is 2500 kg with the landing gear shaft deflection of 0,00164 meter and the stress of 298 MPa. Simulation in this study was conducted by using ANSYS 2014, where this software provides load, deflection and stress analysis. It is found that the analysis of manual calculation and software-based calculation shows only little difference. Keywords : Aircraft N-219, Landing Gear, Shaft, Strenght analyze